Detection of and response to gender-based violence: a quality improvement project across three secondary mental health services in London - Roxanne C. Keynejad; Theo Boardman-Pretty; Sarah Barber; John Tweed; Emily Forshall; Alice Edwards; Joshua Shotton; Claire A. Wilson (BJPsych Bulletin)
Aims and method Our team of core and higher psychiatry trainees aimed to improve secondary mental health service detection of and response to gender-based violence (GBV) in South East London. We audited home treatment team (HTT), drug and alcohol (D&A) service and in-patient ward clinical records (n = 90) for female and non-binary patients. We implemented brief, cost-neutral staff engagement and education interventions at service, borough and trust levels before re-auditing (n = 86), completing a plan–do–study–act cycle.